Penerapan Standar Operasional Prosedur (SOP) dalam Layanan Administrasi di SMK Negeri 3 Makassar - Henri, Henri; Nasir, Nasir (Majalah Ilmiah METHODA, 2025)
The implementation of Standard Operating Procedures (SOP) is one of the strategic efforts to improve the quality of administrative services in the school environment. However, the successful implementation of SOPs does not only depend on the existence of formal documents, but also on the consistency of implementation and support of other supporting systems. This study aims to analyze how SOPs are implemented in administrative services at SMK Negeri 3 Makassar and identify supporting and inhibiting factors for its implementation. This study uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, direct observation, and documentation studies. The results of the study show that SOPs have been compiled and socialized in various service units, such as correspondence, filing, staffing, and student services. In the personnel and finance unit, the implementation of SOPs is going quite well and consistently. However, in the student service unit, the implementation still faces obstacles such as high workload, staff limitations, weak internal supervision, and the lack of optimal use of information technology. The recommendations from this study include the need for periodic training for administrative staff, strengthening monitoring and evaluation systems, and digitizing administrative processes as an effort to improve service efficiency and accountability. Thus, the consistent implementation of SOPs and supported by an adequate support system will be able to strengthen the quality of administrative governance in schools.